Directions of the relationship between substance use and depressive symptoms from adolescence to young adulthood - Wilkinson, Andra L. (Addict Behav, 2016)
PURPOSE: Both substance use and depression are common in adolescence and often comorbid. Past research has produced conflicting results on whether there is a temporal relationship and if so, in which direction it operates and how it may vary by sex. The purpose of this paper is to explore the longitudinal, potentially bidirectional, relationships between high-frequency substance use and depressive symptoms from adolescence into young adulthood for males and females. METHODS: Using data from the National Longitudinal Study of Adolescent to Adult Health we investigated longitudinal associations between high frequency substance use (alcohol, cigarettes, and marijuana) and depressive symptoms. The linear mixed effects models were stratified by sex and used a lagged measure of the dependent variable to test temporal relationships. A random intercept was used for respondent ID. RESULTS: Increases in depressive symptoms were significantly associated with a later increase of about a half day in marijuana use frequency for males and nearly a two day increase in smoking frequency for females. Conversely, increases in smoking frequency were significantly associated with approximately a 0.6-point increase for females and 0.4-point increase for males in depressive symptoms at a later wave. CONCLUSIONS: Results indicate a bidirectional relationship between smoking and depressive symptoms for females. For males, there was evidence supporting self-medication with marijuana and for smoking being associated with later increases in depressive symptoms. Results inform how substance use and depression screening, prevention and treatment efforts should be paired and targeted for males and females.